The Relationship Between Government Finances and Fiscal Decentralization in Mojokerto Regency - Andhika Pradana, Dicky; Hany Fanida, Eva; Anita Fitrie, Revienda (Journal of Development Economic and Social Studies, 2026)
This study aims to explore the financial relationships between the central and regional governments and their impact on the implementation of fiscal decentralization in Mojokerto Regency. The focus of this study covers Regional Original Revenue (PAD), transfer funds, including the General Allocation Fund (DAU), Special Allocation Fund (DAK), and Revenue Sharing Fund (DBH), as well as other legitimate regional revenue sources. The methodology employed is qualitative with a descriptive approach, utilizing secondary data analysis derived from regional budget (APBD) documents, regional financial reports, and relevant regulations. The study's findings indicate that transfer funds remain a major component of regional revenue, contributing approximately 64.8%, while PAD contributes 31.4%. This reflects the importance of financial relations between the central and regional governments in supporting fiscal capacity and regional development, despite relatively low fiscal independence. Furthermore, the potential decline in transfer funds poses a challenge to regional financial stability. Therefore, optimizing PAD, increasing efficiency in financial management, and strengthening transparent and accountable governance are crucial to support sustainable fiscal decentralization.